Dihydrogen H2 steady state in α-radiolysis of water adsorbed on PuO2 surface - Venault, Laurent; Deroche, Arnaud; Gaillard, Jérémy; Lemaire, Olivier; Budanova, Natalia; Vermeulen, Jackie; Maurin, Jérôme; Vigier, Nicolas; Moisy, Philippe (Radiation physics and chemistry (Oxford, England : 1993), 2019)
Radiolysis of water adsorbed on PuO2 surface has been the subject of several studies but still remains poorly understood. The present study brings new experimental results helping to further understand the phenomena occurring at PuO2 surface. Radiolysis of adsorbed water on PuO2 surface leads to the reach of a steady state in hydrogen content when relative humidity is kept constant implying an equilibrium between generation and consumption of hydrogen. The influences of specific surface area, relative humidity, PuO2 dose rate and composition of the atmosphere (Ar vs air) on hydrogen generation were investigated. A significant evolution of the hydrogen generation kinetics was observed upon PuO2 surface aging. This result might be related to an evolution of the surface physicochemical state induced by a long-term storage in H2O/H2/O2 atmosphere. The surface evolution modifies the equilibrium between generation and consumption of hydrogen. Several annealing thermal treatment were necessary to retrieve H2 accumulations kinetics similar to the ones obtained with the same sample as freshly prepared. This indicates an important evolution of PuO2 surface and subsurface. A mechanism is described to explain the surface evolution and its effect on H2 accumulation through radiolysis of adsorbed water. •H2 formed under α-radiolysis of water sorbed on PuO2 surface reaches a steady state after several days.•The initial rate R0 increases with dose rate, relative humidity and specific surface area.•H2 steady-state concentration increases with dose rate, relative humidity and specific surface area.•Hydrogen accumulation and consumption reach the same steady state and conduct to a kinetic model.•The rates of hydrogen accumulation increase with long term storage and is restored by annealing treatments.